Regional specialisation and location of industrial activity in accession countries - Iulia Traistaru; Peter Nijkamp; Simonetta Longhi (European Regional Science Association (ERSA), 2002)
Central and East European economies have experienced since 1990 increasing integration with the European Union via trade and foreign direct investments. The spatial implications of this process have been, so far, little investigated. This paper identifies and explains the effects of economic integration on patterns of regional specialisation, location of industrial activity and regional growth in accession countries. We address the following research questions: Have patterns of regional specialisation changed in the period 1990-1999? Does greater specialisation imply greater polarisation? Has relocation of manufacturing activity taken place? What is the relationship between regional specialisation and growth? We find evidence suggesting a tendency of increasing absolute and relative regional specialisation in Bulgaria, Romania and Slovenia and decreasing specialisation in Hungary and Estonia. We also find relocation and increasing geographic concentration of manufacturing activity, of different magnitude though, in all five countries mentioned above. Bilateral differences between the industrial structures of pairs of countries indicate that Romania and Bulgaria have become more similar in the period 1991-1994 but are diverging since 1995. Also, industrial structures in Romania and Slovenia and Bulgaria and Slovenia, respectively, are diverging. Industrial structures in Romania and Bulgaria are more similar to each other compared to Slovenia's. Our research results suggest that regional specialisation is negatively related to regional GDP and unemployment rates and that lower growth of regional GDP per capita is associated with higher unemployment rates.
Keywords: 330